IDENTIFIKASI GUNUNG API PURBA PENDUL DI PERBUKITAN JIWO, KECAMATAN BAYAT, KABUPATEN KLATEN – JAWA TENGAH - Bronto, Sutikno (Pusat Survei Geologi, 2010)
According to previous workers, Mount Pendul were considered as micro gabbro intrusive rocks. However, in the present quarry area pillow basaltic lava flows are exposed in the eastern slope of the hill. The lava was erupted through a paleoconduit below deep sea water, having massive to autoclastic breccias, obsidian in the glassy rims and gradually changes to apanetic texture in the inner part. Microscopically, the obsidian is devitrified to become spherulites, while to the inner part the basaltic rock gradually changes from vitrophyric to hypocrystallin porphyritic textures. On the basis of the volcanic geology idea, the association of those basic intrusive and extrusive rocks is believed to be a remnant of Pendul Paleovolcano that has been eroded through the time. The age of volcanisms, particularly in Bayat area and regionally in the Southern Mountains, can be divided into four periods, e.g. Paleocene, Late Eocene - Early Oligocene, Early Miocene and Middle Miocene. However, based on the range of radiometric ages and predominant volcanic rocks in the Southern Mountains, it is suggested that volcanisms had been continued from Late Eocene to Early Miocene. The oldest (Paleocene) and the youngest (Middle Miocene) radiometric ages should be verified in order to develop researchs on volcanism and tectonics in the Southern Mountains, Java.Keywords: bayat, java, jiwo, paleovolcano, pendul, southern mountains